The Concept of Nyarira Lagu in Jineman Maduswara, A New Sindhenan Tradition Composed by Peni Candra Rini - Rini, Peni Candra; Sukerta, Pande Made (Gelar: Jurnal Seni Budaya, 2022)
"Maduswara" is a new musical work whose creation is based on memoirs, or the journey of Peni Candra Rini's in interpreting the sounds she has encountered. The memoir in question is the composer's memory from childhood when he first knew the tembang macapat, which was later termed as wiji tembang. The song continues to develop into a sound journey when the artist grows up, enters a formal karawitan school, and becomes a tembang lecturer in the musical department at the Indonesian Institute of the Arts Surakarta.The method of creation used is through several stages inspired by the composer's personal process, namely (1) reflection, (2) dialectics, (3) giving the tone of expression, (4) determining the form, (5) determining the medium, (6) compiling compositional musical notation, (7) transmedium, (8) practice, (9) improvisation.These steps of creation finally found a concept of nyarira lagu which was built on 5 indicators, namely; (1) language, (2) voice, (3) expression, (4) spirituality, and (5) improvisation